Penerapan Model Problem Based Learning (PBL) dalam Meningkatkan Hasil Belajar Peserta Didik pada Materi Kedudukan, Hak dan Kewajiban Warga Negara di Kelas X – 7 SMA Negeri 3 Rantau Utara Tahun Ajar 2024 – 2025 - Sarinah D. Silalahi (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The formulation of the problem in this research is whether implementing the Problem Based Learning (PBL) model can improve the learning outcomes of class X - 7 students of SMA Negeri 3 Rantau Utara in the 2024 - 2025 academic year. This study aims to improve problem-solving knowledge in order to improve student learning outcomes through the Problem Based Learning (PBL) model in order to improve the learning of class X - 7 students of SMA Negeri 3 Rantau Utara. This type of research is classroom action research using quantitative techniques, namely research that explains the efforts made to increase student interest in learning in the student learning and teaching process. The subjects in this study were all students in grades X – 7 consisting of 36 students. From the results of data analysis, it can be seen that the application of the problem based learning model can actually increase student activity as seen from the increase in student activity and student learning outcomes in learning. This can be seen from the learning outcomes through the post-test in cycle I, where the number of students who completed was 20 people or 56% while the learning outcomes in cycle II, students who completed were 26 people or 72%. In cycle III, the number of students who completed was 35 people or 97%. So the increase from cycle I to cycle II reached 16%. The increase has not reached the achievement so that cycle III was carried out to achieve an increase of 25% resulting in an achievement of 97% as many as 35 students with a complete value. During the learning.